Queueing Theory Applications in Real-World Scenarios - Pathak, Narendra (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Queueing theory, a mathematical framework for analyzing waiting lines, has significant applications across various real-world scenarios. In telecommunications, it optimizes data packet flow to minimize latency, while in customer service, it helps manage call center operations and retail checkout processes, enhancing customer satisfaction through reduced wait times. In manufacturing, queueing models streamline production lines and inventory management, preventing bottlenecks and maximizing resource utilization. The transportation sector benefits from improved traffic flow analysis, leading to efficient traffic light patterns and public transit scheduling. Healthcare applications include optimizing emergency room operations and appointment systems to enhance patient care. Additionally, queueing theory plays a critical role in computer systems, aiding in server management and database optimization, as well as in hospitality settings where it improves guest check-in processes and restaurant efficiency. Event management also leverages these principles to streamline entry and service at large gatherings. By applying queueing theory, organizations can gain insights that enhance operational efficiency, optimize resource allocation, and improve overall service delivery, demonstrating its versatility and importance in addressing challenges across diverse industries.